ANALISIS PENGARUH UPAH, PENDIDIKAN, JUMLAH TANGGUNGAN KELUARGA DAN STATUS PERKAWINAN TERHADAP CURAHAN JAM KERJA WANITA DI KECAMATAN PEDURUNGAN DAN KECAMATAN TEMBALANG KOTA SEMARANG - Marita Praba; Waridin Waridin (Diponegoro Journal of Economics, 2013)
This study aimed to analyze the effect of wages, education, number of family dependants and marital status to outpouring working hours of the worker women at two sub-districts in the city of Semarang, Pedurungan and Tembalang. The method used in collecting primary data by cluster sampling and accidental sampling. The study took a sample of 100 respondents. The analysis tool used is multiple linear regression with the outpouring working hours of worker women as the dependent variable while the wage rate (Rupiah), education level (years), number of family dependants (person) and marital status (married and unmarried/widowed) as independent variables. After tested with irregularities classical assumptions test, the results showed that data distributed normally and did not obtained a deviation. Based on the calculation of E-views 5.0 obtained the F values was 38,20380 with F probability of 0,000000. with the significance 0,05 obtained F table value is 2,70, then F value (38,20380) > F table (2,70) or the probability of 0,000000 F showed smaller than 0,05 so it can be concluded that the four variables are the wage rate, education level, number of family dependants, and status marriage together influence the outpouring of work hours. Partially, all of the variables were significant. Coefficient of determination value of 0,600509 which means that outpouring working hours of the worker women can be explained by the variable factors of wages, education, number of family dependants and marital status of 60,0509 percent. While the remaining 39,9491 per cent of outpouring working hours of the worker women is explained by other variables not included in the analysis model in this study.